A Descriptive Study of Social Anxiety in Islamic Secondary Education Students - Gilang Nauval Umam; muhammad muhajirin; Feida Noorlaila Isti’adah (Edupotensia Foundation, 2026)
Social anxiety is a psychological problem commonly experienced by adolescents and has the potential to hinder their social and academic development. Students who experience social anxiety tend to fear negative evaluation, avoid social interactions, and experience stress in various social situations in the school environment. This study aims to determine the general description of social anxiety in students at Madrasah Aliyah (MA) Mathla'ul Falah Wakap, examine differences based on gender, and examine the implications of guidance and counseling services in addressing students' social anxiety. This study used a quantitative approach with descriptive methods. The subjects were MA Mathla'ul Falah Wakap students selected using a sampling technique in accordance with the characteristics of the study. The instrument used was a social anxiety scale developed based on the aspects of fear of negative evaluation, social avoidance and stress in new situations, and social avoidance and stress in situations with familiar people. Data analysis was conducted using descriptive statistics. The results showed that in general, students' social anxiety levels were in the moderate category, with fear of negative evaluation as the most dominant aspect. In addition, there were differences in social anxiety levels based on gender, where female students tended to have higher levels of social anxiety than male students. The findings of this study indicate the important role of guidance and counseling services in preventive and curative efforts to help students manage social anxiety adaptively in the school environment.